In vivo role of Candida albicans β‐hexosaminidase (HEX1) in carbon scavenging. Issue 5 (14th July 2015) - Ruhela, Deepa; Kamthan, Mohan; Saha, Paramita; Majumdar, Subeer S.; Datta, Kasturi; Abdin, Malik Zainul; Datta, Asis
Abstract The capability to utilize of N‐acetylglucosamine (GlcNAc) as a carbon source is an important virulence attribute of Candida albicans. But there is a lack of information about the in vivo source of GlcNAc for the pathogen within the host environment. Here, we have characterized the GlcNAc‐inducible β‐hexosaminidase gene (HEX1) of C. albicans showing a role in carbon scavenging. In contrast to earlier studies, we have reported HEX1 to be a nonessential gene as shown by homozygous trisomy test. Virulence study in the systemic mouse murine model showed that Δhex1 strain is significantly less virulent in comparison to the wild‐type strain. Moreover, Δhex1 strain also showed a higher susceptibility to peritoneal macrophages. In an attempt to determine possible substrates of Hex1, hyaluronic acid (HA) was treated with purified Hex1 enzyme. A significant release of GlcNAc was observed by gas chromatography‐mass spectrometry analysis analysis suggesting HA degradation. Interestingly, immunohistochemistry analysis showed significant accumulation of HA in the mice kidney infected with the wild‐type strain of C. albicans. Northern blot analysis showed that C. albicans HEX1 is expressed during mice renal colonization. Thus, C. albicans can obtain GlcNAc during organ colonization by secreting Hex1 via degradation of host HA.